The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1213/00000539-199109000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Breathing Pattern and Occlusion Pressure Waveform in Humans Anesthetized With Halothane or Sevoflurane

Abstract: To examine the ventilatory effects of sevoflurane, breathing pattern, airway occlusion pressure waveform, and the mechanical variables of the respiratory system were determined in seven subjects anesthetized with sevoflurane and in an additional seven subjects anesthetized with halothane. All patients breathed 1 MAC of anesthetic using oxygen as the carrier gas, and the measurements were performed in the absence of surgical stimulation. The durations of inspiration and expiration were significantly longer duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…3-5). No difference in HBIR EE activity was observed between halothane and sevoflurane, which agrees with findings in adults (21). Although infants were premedicated with atropine, an agent known to decrease vagal activity, the oral dose of 20 µg/kg is minimal compared with the intravenous dose required for ablation of a vagal response in dogs (1.5 mg/kg) (34).…”
Section: Potentially Confounding Factorssupporting
confidence: 81%
See 1 more Smart Citation
“…3-5). No difference in HBIR EE activity was observed between halothane and sevoflurane, which agrees with findings in adults (21). Although infants were premedicated with atropine, an agent known to decrease vagal activity, the oral dose of 20 µg/kg is minimal compared with the intravenous dose required for ablation of a vagal response in dogs (1.5 mg/kg) (34).…”
Section: Potentially Confounding Factorssupporting
confidence: 81%
“…The HBIR persists beyond the newborn period (36,44) and remains active even at 1 yr of age (37), although longitudinal measurements show a reduction in activity from 90% in early infancy (36,44) to 50% at 1 yr of age (37). Unlike in anesthetized adults, in whom there is no response (21), end-expiratory airway occlusion (EEO) during tidal breathing, a maneuver that removes the inspiratory-inhibitory effect of lung inflation, results in a prolongation of inspiration by ϳ20% in anesthetized infants (3).…”
mentioning
confidence: 99%
“…Clark and Euler [4] suggested that the difference of respiratory timing among inhalation anesthetics may depend on the degree of strength of the Hering-Breuer inflation reflex by those drugs. Several studies have reported the ventilatory effects of inhalation anesthetics from the aspect of reflex actions [3,7,9,10]; however, only a few studies have been performed as to the effects of recent available inhalation anesthetics on vagal inputs originating from SARs.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the concentration of sevoflurane was followed by a similar decrease in Rrs in both groups. There was also a reduction in tidal volume with increased sevoflurane, which may be related to a great depression of intercostal muscle function with increasing depth of anesthesia (20). There was a significant tachypnea in both groups, which has recently been reported after induction of sevoflurane in adults (21).…”
Section: Discussionmentioning
confidence: 56%